Acidification of uterine epithelium during embryo implantation in mice†. Issue 1 (23rd December 2016) - Xiao, Shuo; Li, Rong; El Zowalaty, Ahmed E.; Diao, Honglu; Zhao, Fei; Choi, Yongwon; Ye, Xiaoqin
Abstract: Uterine luminal epithelium (LE) is essential for establishing uterine receptivity. Previous microarray analysis revealed upregulation of Atp6v0d2 in gestation day 4.5 (D4.5) LE in mice. Realtime PCR showed upregulation of uterine Atp6v0d2 starting right before embryo attachment ∼D4.0. In situ hybridization demonstrated specific uterine localization of Atp6v0d2 in LE upon embryo implantation. Atp6v0d2 encodes one subunit for vacuolar-type H + -ATPase (V-ATPase), which regulates acidity of intracellular organelles and extracellular environment. LysoSensor Green DND-189 detected acidic signals in LE and glandular epithelium upon embryo implantation, correlating with Atp6v0d2 upregulation in early pregnant uterus. Atp6v0d2 −/− females had significantly reduced implantation rate and marginally reduced delivery rate from first mating only, but comparable number of implantation sites and litter size compared to control and comparable fertility to control from subsequent matings, suggesting a nonessential role of Atp6v0d2 subunit in embryo implantation. Successful implantation in both control and Atp6v0d2 −/− females was associated with uterine epithelial acidification. No significant compensatory upregulation of Atp6v0d1 mRNA was detected in D4.5 Atp6v0d2 −/− uteri. To determine the role of V-ATPase instead of a single subunit in embryo implantation, a specific V-ATPase inhibitor bafilomycin A1 (2.5 μg/kg) was injected via uterine fat pad on D3 18:00 h. This treatment resulted in reduced uterine epithelial acidification, delayed implantation, and reduced number of implantation sites. It also suppressed oil-induced artificial decidualization. These data demonstrate uterine epithelial acidification as a novel phenomenon during embryo implantation and V-ATPase is involved in uterine epithelial acidification and uterine preparation for embryo implantation. Abstract : Our findings that mouse uterine epithelium becomes more acidic upon embryo implantation initiation and suppression of uterine epithelial acidification adversely affects embryo implantation provide a novel direction for understanding mechanisms in establishing uterine receptivity.